2017
DOI: 10.1097/mao.0000000000001583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Behavioral Problems in Children With Hearing Loss

Abstract: Objective To compare the prevalence of disruptive behavior problems between preschool-aged children with hearing loss and normal hearing. Study design Cross-sectional study Setting Tertiary academic center Patients Caregivers of children (2–5 years old) with normal hearing (NH) (n=39), hearing loss using hearing aid(s) (HA) (n=29), or cochlear implant(s) (CI) (n=21). Intervention(s) Demographic information and a mental health history were obtained. Child behavior and language development were assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…There is a significant gap, however, in the delivery of behavioral interventions to parents of children who are DHH, though the need for these interventions has been articulated ( Fellinger, 2011 ; Stevenson et al, 2011 ). In our previous research with parents of preschool-age children who were DHH and used HA and/or CI ( Fiorillo et al, 2017 ), we confirmed others' findings that parents of young children who were DHH ( n = 50) were significantly more likely to report concerns about child emotional or behavioral problems, compared with parents of children with typical hearing ( n = 39). Based on a structured clinical diagnostic interview, nearly half of the children who were DHH met the criteria for oppositional defiant disorder, one of the most common behavioral disorders in children; in comparison, only one in five children with typical hearing met criteria.…”
Section: Parenting Behaviors As a Target Of Intervention: Behavioral ...supporting
confidence: 88%
“…There is a significant gap, however, in the delivery of behavioral interventions to parents of children who are DHH, though the need for these interventions has been articulated ( Fellinger, 2011 ; Stevenson et al, 2011 ). In our previous research with parents of preschool-age children who were DHH and used HA and/or CI ( Fiorillo et al, 2017 ), we confirmed others' findings that parents of young children who were DHH ( n = 50) were significantly more likely to report concerns about child emotional or behavioral problems, compared with parents of children with typical hearing ( n = 39). Based on a structured clinical diagnostic interview, nearly half of the children who were DHH met the criteria for oppositional defiant disorder, one of the most common behavioral disorders in children; in comparison, only one in five children with typical hearing met criteria.…”
Section: Parenting Behaviors As a Target Of Intervention: Behavioral ...supporting
confidence: 88%
“…Despite the wide range these estimates present, they do suggest that the risk of mental disorders might be higher among deaf children and adolescents compared with hearing children and adolescents. [1][2][3][4][5][6][7][8][9] Mental and neurodevelopmental disorders include intellectual disabilities, autism spectrum disorder, mood disorders, schizophrenia spectrum and psychotic disorders and trauma and stressrelated disorders, classified by the Diagnostic…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…There remains a need to catalogue how other outcomes vary between these groups, including quality of life and educational attainment, as noted by Bond et al (2009b). Furthermore, provision of HAs or CIs to children with more residual hearing to lose than traditional CI candidates might also affect outcomes that may not be routinely measured in the clinic such as spatial hearing, listening effort and fatigue, psychosocial outcomes, vestibular function, tinnitus, and music perception (Dorman et al 2016; Fiorillo et al 2017; Ganek et al 2020; Killan et al 2018; Looi 2014; Winn 2007; Wong et al 2017). While optimizing these outcomes might not be the primary goal when choosing a listening device, they are important outcomes to assess following the provision of listening devices as they can impact children’s quality of life, mental health, social and recreational participation, sleep, and educational attainment (Camarata et al 2018; Fellinger et al 2015, Inoue et al 2013; Smith et al 2019; Vecchiato et al 2013).…”
Section: Introductionmentioning
confidence: 99%